2005
DOI: 10.1080/10647440500148024
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Laboratory IgM Testing for Toxoplasma gondii in Pregnancy: A 20‐Year Experience

Abstract: OBJECTIVE: This study was performed to review the clinical utility of commercial laboratory Toxoplasmosis-specific IgM testing during pregnancy and outcomes of the gestation at our institution. METHODS: A retrospective review of all women referred for suspected acute Toxoplasma gondii infection during pregnancy from 1984 through 2004 was performed. Women were diagnosed with suspected acute toxoplasmosis based on commercial laboratory serologic antibody testing. All women had blood sent to a recognized referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…However, this is an unlikely scenario because in the longitudinal component of this study, with a total of 116 women sampled at each of the three trimesters or during each of the first and second trimesters, 22 (19.0%) were seropositive for IgM for the first time during their pregnancies. It is pertinent, however, to mention that one cannot always equate the detection of T. gondii-specific IgM to acute infection since commercial test kits have yielded false-positives (41). Although cats are the primary source of oocysts that cause human and livestock infections (3,5,30), in our study, household cats or handling of cat litter were not found to be signif- icantly associated with T. gondii infection in pregnant women.…”
Section: Discussionmentioning
confidence: 53%
“…However, this is an unlikely scenario because in the longitudinal component of this study, with a total of 116 women sampled at each of the three trimesters or during each of the first and second trimesters, 22 (19.0%) were seropositive for IgM for the first time during their pregnancies. It is pertinent, however, to mention that one cannot always equate the detection of T. gondii-specific IgM to acute infection since commercial test kits have yielded false-positives (41). Although cats are the primary source of oocysts that cause human and livestock infections (3,5,30), in our study, household cats or handling of cat litter were not found to be signif- icantly associated with T. gondii infection in pregnant women.…”
Section: Discussionmentioning
confidence: 53%
“…A lack of avidity test in the study by Liesenfeld may also have resulted in a higher proportion of acute infection diagnoses. In a study on the clinical utility of positive IgM test results in pregnant women obtained at their NRLs, Garry et al found the IgM test to have a very low PPV (6%) for an acute infection when their serum underwent confirmatory testing at PAMF-TSL (13). Furthermore, the sensitivity, specificity, PPV, and negative predictive value (NPV) of PAMF-TSL IgM ELISA in their study were 100%, 83%, 25%, and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, some immunoenzymatic tests detecting anti-Toxoplasma IgM antibodies seem to have low positive predictive values and can yield discrepant results (7,9,17,19). Therefore, seroconversion is often confirmed only once IgG is detected (5,9,13).…”
Section: Discussionmentioning
confidence: 99%